Utilization of Parijoto (Medinilla speciosa Blume) Fruit Extract as a Counterstain in Gram Staining of Escherichia coli: Pemanfaatan Ekstrak Buah Parijoto (Medinilla speciosa Blume) Sebagai Counterstain Pada Pewarnaan Gram Escherichia coli - Sisilia Pratiwi; Indah Sari; Aristoteles Aristoteles; Rossa Veronneca; Tesa Amantasya (Universitas Muhammadiyah Sidoarjo, 2025)
The use of Gram staining using synthetic dyes such as safranin has the disadvantage of being more expensive and can be harmful to health and damage organs if exposed repeatedly. Parijoto fruit has an anthocyanin content of 0.43 ppm. In terms of quality, Parijoto fruit contains active compounds such as flavonoids, tannins, saponins, and alkaloids. The anthocyanin content in Parijoto fruit is a secondary metabolite compound that can produce red color in Parijoto fruit so that it can be used as a natural dye. This research to determine the difference in interpretation of staining results using parijoto fruit extract as a substitute for safranin in Gram staining. This research method using a cross-sectional research design, posttest-only control group design research type, this study was conducted in the microbiology laboratory of Muhammadiyah Ahmad DahlanUniversity, Palembang. The sample used in this study was 32 preparations. Data analysis was carried out using the Wilcoxontest. The study results showed good quality results in preparations using safranin as much as 81%, less good (18%), and not good (0%). Meanwhile, good quality was obtained in preparations using parijoto fruit extract as much as 75%, less good (25%), and bad (0%). Based on statistics, there was no significant difference between parijoto fruit extract and safranin in gram staining of 0.705 (p>0.05). The conclusion of this study is parijoto fruit has good quality to be used as a natural dye.